2004
DOI: 10.1524/ract.92.12.945.55107
|View full text |Cite
|
Sign up to set email alerts
|

Determination of natural radioactivity in building materials used in the Karachi area by γ-ray spectrometry and INAA

Abstract: Natural radioactivity / Primordial natural radionuclides / Indoor radioactive pollution / γ -ray spectrometry / INAA Summary. Samples of sand, stone and manufactured building materials collected from Karachi area have been analyzed for the primordial natural radionuclides 238 U, 232 Th and 40 K using γ -ray spectrometry. The uranium and thorium contents have also been determined by instrumental neutron activation analysis (INAA). The specific activities in these materials, having a radium equivalent activity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A semi-circle of barren peaks of the Karakoram Mountains about 4,500 m high enclose the valley. Similar studies (Zaidi et al 2004) have also been conducted for the determination of natural and anthropogenic radionuclides in the sand, stone, and building manufacturing material from Karachi and in the soil of Punjab (Tahir et al 2005(Tahir et al , 2006, Pakistan, and in other countries (Mitrovic et al 2009). The quantification of ␥-emitting radionuclides is not only important from the dose calculation point of view, but some ␥-ray emitting radionuclides such as 7 Be, 137 Cs, and 210 Pb act as useful tracers in different studies; i.e., the ratio of 134 Cs/ 137 Cs can be used to identify the origin of contamination (Demeny et al 2002).…”
Section: Introductionmentioning
confidence: 80%
“…A semi-circle of barren peaks of the Karakoram Mountains about 4,500 m high enclose the valley. Similar studies (Zaidi et al 2004) have also been conducted for the determination of natural and anthropogenic radionuclides in the sand, stone, and building manufacturing material from Karachi and in the soil of Punjab (Tahir et al 2005(Tahir et al , 2006, Pakistan, and in other countries (Mitrovic et al 2009). The quantification of ␥-emitting radionuclides is not only important from the dose calculation point of view, but some ␥-ray emitting radionuclides such as 7 Be, 137 Cs, and 210 Pb act as useful tracers in different studies; i.e., the ratio of 134 Cs/ 137 Cs can be used to identify the origin of contamination (Demeny et al 2002).…”
Section: Introductionmentioning
confidence: 80%
“…Akhtar et al (2004c) also reported activity concentrations of the relevant radionuclides for the Nuclear Institute for Agriculture and Biology (NIAB) soil as 40 K, 614-671 Bq kg −1 , 226 Ra, 29-33 Bq kg −1 , and 232 Th, 52-60 Bq kg −1 . Zaidi et al (2004) reported in samples of sand, stone and building materials collected from Karachi radium equivalent activities less than 370 Bq kg −1 . Khan et al (2005) reported activity concentrations of 226 Ra, 232 Th and 40 K in sand samples collected from North-West Frontier Province (NWFP) as 37-52, 53-68 and 680-784 Bq kg −1 , respectively.…”
Section: Summary Of the Resultsmentioning
confidence: 99%